The Use of Deepfake-Powered Virtual Anchors in Live Commerce Influences Women’s Shopping Behaviour in the Southeast Asian E-Commerce Industry - Jiang, Lifen; Loahavilai, Piang-or; Udomwong, Piyachat (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026DO - 10.14505/tpref.v17.1(37).10, 2026)
This study explores the introduction of deepfake technology in live commerce, particularly the effects of using virtual anchors (AI live streamers) to increase engagement and improve sales conversion rates. Realistic high-quality virtual anchors were enabled using DeepFaceLab that generates real-time facial animation, while Vizard Virtual Reality Software is developed for an interactive and engaging live streaming environment. Three hundred women aged 18-50 from Southeast Asia assessed the effectiveness of these technologies. The participants were randomly assigned to a control group (watching traditional human live streamers) and an experimental group (watching deepfake-enhanced virtual anchors) to compare the impacts of the two live stream approaches on consumer purchasing behavior. Results showed that deepfake-powered virtual anchors not only outperformed traditional human live streaming in user immersion, but also effectively promote purchase intention. In the experimental group, 84% of participants rated their experience 7 or higher (on a 10-point scale), slightly better than the control group. Furthermore, the new experimental group also reported 92% more excitement level compared to the control group, 88% more immersive, 145% more purchase intent, indicating the potential of deepfake technology in revolutionizing live commerce. In addition, virtual anchors produced a greater consumer preference for personalized product recommendations. Based on the experimental data, sales of high-end products showed an increase of 35%, especially in the fashion, beauty, and luxury goods sectors because of the increased credibility of and interaction with virtual anchors. Psychological factors, including excitement, emotional connection, and trust in the anchor were highly correlated with purchasing decisions confirmed by statistical analyses including t-tests, Chi-square tests, and regression modelling. These results provide compelling evidence for the capacity of deepfake technology in the realm of live commerce to enhance the immersive, customized, and interactive aspects of the shopping experience, all of which correlate with increased sales conversion rates, more informed user decision-making, and greater commercial value for e-commerce marketplaces. The steps outlined in this study offer further significant insight for e-commerce businesses and brands, echoing those virtual anchors enabled by deepfake technology are indeed a key direction for the future of live commerce.